Prediksi Penerimaan Layanan Insurance Technology (Insurtech) Dengan Menggunakan Technology Acceptance Model (TAM) - Gusi Putu Lestara Permana; Satria Yogananda; I Gusti Ngurah Darma Paramartha (UNHI Press, 2023)
This study aims to determine the effect of perceived convenience, perceived usefulness, perceived risk, and partial relative advantage on acceptance of Insurance Technology (Insurtech) services. The sample in this study were 80 people. From the research results, it was found that perceived ease of use had a significant positive effect on acceptance of Insurance Technology (Insurtech) services, perceived usefulness had a significant positive effect on acceptance of Insurance Technology (Insurtech) services, perceived risk had a significant negative effect on acceptance of Insurance Technology (Insurtech) services, and relative advantage significant positive effect on acceptance of Insurance Technology (Insurtech) services. Suggestions that can be given as material for further research are hoped to be able to add other variables that can affect acceptance of Insurance Technology (Insurtech) services such as the influence of external variables on previous experience, subjective norms and so on. Due to the nature of this research, the influence of independent variables with the dependent variable is only 43 .2%.